2014
DOI: 10.1111/evj.12267_145
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Kinematics During Repeated Jumping

Abstract: This publication is a compilation of all Research Abstracts presented at the Ninth International Conference on Equine Exercise Physiology. Unlike previous ICEEP conferences there will not be a conference proceedings of full length manuscripts. These abstracts succinctly summarise a wide array of investigations relevant to the equine athlete, and will be useful to veterinarians and others involved in management of horses used for sport, work and competition. The abstracts encompass the topics of Applied Physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, successful horses were found to take off further from the fence than unsuccessful horses during a puissance competition (Powers, 2002). Wejer et al (2013) reported that equine jump kinematics were also altered by experience and training, whilst Rorigues et al (2014) found a decrease in jumping efficiency when the number of jumps increased. Anatomically, equines and canines differ, but it is reasonable to postulate that changes between hurdle distance will affect canine jump kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, successful horses were found to take off further from the fence than unsuccessful horses during a puissance competition (Powers, 2002). Wejer et al (2013) reported that equine jump kinematics were also altered by experience and training, whilst Rorigues et al (2014) found a decrease in jumping efficiency when the number of jumps increased. Anatomically, equines and canines differ, but it is reasonable to postulate that changes between hurdle distance will affect canine jump kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Neck, thoracic and lumbar motion influenced subjective grading of the jumping technique, and although higher ratings were only weakly related to longer take‐off distances , the probability of success in free jumping increased with increasing take‐off distance . Increased velocity was found to reduce free jumping success, and increasing the number of jumping efforts decreased take‐off and landing distances and the height of the forelimb, withers and croup over the fence . Much work is still needed in this area to fully appreciate the demands on the horse fully, depending on capability, discipline, fence type, environmental factors and competition level.…”
Section: Equine Locomotion and Sports Performancementioning
confidence: 99%